Arcane Language of Human Emotions: Envy and Jealousy in Academia - Mahendra Kumar; Anita Kumari; Khina Sharma (National Journal of Community Medicine, 2022)
Jealousy and Envy are essential part of human emotions and behavior. In today’s fast-moving world where everyone is in rush to cut-throat competition, it is more important to discuss these emotions than ever before. Jealousy and envy somewhere connected. Jealousy is a practice to defend something that is owned and threatened whereas envy is a tendency to obtain something that does not own by one.  Jealousy and envy develop naturally and also test their character by the response they give due to emotional burnout. Sometimes these situations broke and turn healthy competition into a rivalry at cost of long-standing personal relationships. Jealousy and envy include compound emotional experiences during the exercises to acquire or not lose something desirable. The impact of envy and jealousy is not assessed in academia and research area moreover it is important to understand that envy is often hidden in the classroom context, but it must still be discussed.